Antiproliferative effects of protopanaxadiol ginsenosides on human colorectal cancer cells - ZHENG, YAN (D.A. Spandidos, 2013)
Ginsenosides are the main biologically active components of ginseng. In this study, seven types of protopanaxadiol ginsenosides were assessed for their antiproliferative activity on the HCT-116 and HT-29 human colorectal cancer cell lines using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. The experimental results indicated that the native protopanaxadiol ginsenosides Rb1 and Rb2 inhibited the proliferation of the colorectal cancer cells in a dose-dependent manner. The deglycosylation products F2 and CO (from ginsenosides Rb1 and Rb2, respectively) significantly inhibited the growth of the human colorectal cancer cell lines, whereas product C-K (from Rb1 and Rb2) exerted no antiproliferative effects on the cancer cell lines assessed in this study. HT-29 cells were more sensitive to these ginsenosides compared to HCT-116 cells. In addition, the antiproliferative activity of ginsenosides was found to be correlated with the number and type of sugar residues. The potent growth inhibitory effect of protopanaxadiol ginsenosides on cancer cells may be used in the pharmaceutical industry.